Analisis Aplikasi Smartgov Terhadap Pembayaran Pajak - Yuliana, Nesi (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
This study aims to analyze the impact and effectiveness of the SmartGov application on tax payments at the Ampek Nagari Sub-District Office. The study uses a combination of qualitative and quantitative approaches, employing the Technology Acceptance Model (TAM) and Smart PLS statistical analysis. Primary data was collected through interviews and questionnaires distributed to taxpayers, tax officials, and relevant parties. The results show that the SmartGov application provides significant perceived benefits and ease of use for users. The application also receives positive acceptance from users. However, there are some independent indicators that do not directly affect information management. This study provides a better understanding of the use of the SmartGov application in tax payments and offers guidance for local governments in adopting information technology to enhance tax services for the community.